Pengaruh Kualitas Layanan Chatbot GoPay terhadap Kepuasan dan Kepercayaan Pengguna pada Mahasiswa UNISSULA Semarang - Muhammad Didan Naufal; Arina Iftiani; Fikri Shofin Mubarok; Dian Marhaeni Kurdaningsih (INDO PUBLISHING, 2026)
The development of digital technology has encouraged the use of chatbots as customer service tools in digital financial applications, including GoPay. This study aims to examine the influence of user satisfaction and trust on the quality of GoPay chatbot services among UNISSULA Semarang students. A quantitative approach was employed through a survey of 100 students who had used the GoPay chatbot. Data were analyzed using IBM SPSS Version 27. The results indicate that both user satisfaction and trust have a positive and significant effect on chatbot service quality. Simultaneously, these variables explain 71.9% of the variation in chatbot service quality. The findings suggest that chatbot service quality is influenced not only by system performance but also by users’ satisfaction and trust in digital services